Geographic distribution of live births with tetralogy of Fallot in North Carolina 2003 to 2012. Issue 11 (November 2016) - Nelson, Jennifer S.; Stebbins, Rebecca C.; Strassle, Paula D.; Meyer, Robert E.
Abstract : Background: Geographic variation in congenital heart disease is not well‐described. This study uses geographic information systems (GIS) to describe the spatial epidemiology of tetralogy of Fallot (TOF), in North Carolina (NC) and to compare travel time for cases to congenital heart centers in NC. Methods: Using the NC Birth Defects Monitoring Program database, live births with TOF born between 2003 and 2012 were identified. Birth certificates provided demographic variables. A denominator of live births/zip code was obtained from the NC live births database. ArcGIS® software was used to illustrate TOF prevalence by zip code, and SatScanTM was used to identify spatial clusters of TOF cases and to identify changes in cluster location over time. Driving time to each of five NC congenital heart centers was predicted based on road systems information. Results: A total of 496 infants were born with TOF between 2003 and 2012. The prevalence was 4.2/10, 000 live births. A large cluster (330 zip codes, 306 cases) was identified in northeastern NC. Average driving time for each case to closest congenital heart center was: University of North Carolina 37 min, Vident Medical Center 64 min, Duke University 58 min, Carolina's Medical Center 89 min, and Wake Forest Baptist Health 57 min. Overall, average predicted driving time to the nearest congenital heart center was 61 min. Conclusion: Approximately 50 infants/year were born with TOF in NC. One cluster was identified. Further study is necessary to explore potential explanations for the observed case cluster. As interest in regionalization of congenital heart surgery grows, GIS and spatial analysis can become increasingly useful tools for health care planning. Birth Defects Research (Part A) 106:881–887, 2016. © 2016 Wiley Periodicals, Inc.